Hybridization effect on the mechanical properties of curaua/glass fiber composites - Almeida Jr., José Humberto Santos; Amico, Sandro Campos; Botelho, Edson Cocchieri [UNESP]; Amado, Franco Dani Rico (Elsevier, 2013)
The aim of this paper was to evaluate the effect of hybridizing glass and curaua fibers on the mechanical properties of their composites. These composites were produced by hot compression molding, with distinct overall fiber volume fraction, being either pure curaua fiber, pure glass fiber or hybrid. The mechanical characterization was performed by tensile, flexural, short beam, Iosipescu and also nondestructive testing. From the obtained results, it was observed that the tensile strength and modulus increased with glass fiber incorporation and for higher overall fiber volume fraction (%Vf). The short beam strength increased up to %Vf of 30 vol.%, evidencing a maximum in terms of overall fiber/matrix interface and composite quality. Hybridization has been successfully applied to vegetable/synthetic fiber reinforced polyester composites in a way that the various properties responded satisfactorily to the incorporation of a third component. © 2013 Published by Elsevier Ltd. All rights reserved.
Keywords: A. Hybrid; C. Micro-mechanics; D. Mechanical testing; D. Non-destructive testing; Fiber volume fractions; Fiber/matrix interface; Hybridization effects; Mechanical characterizations; Non destructive testing; Polyester composites; Short beam strengths; Glass fibers; Mechanical properties; Mechanical testing; Nondestructive examination; Tensile strength; Fibers